Spectrophotometrical purity and stability testing of a photosensitizer based on an indotricarbocyanine dye - Belko, Nikita V.; Samtsov, Michael P.; Tarasau, Dzmitry S. (Journal of the Belarusian State University. Physics, 2020)
The express method for testing purity and stability of an indotricarbocyanine dye based photosensitizer for photodynamic therapy was developed. Storage of the hydrophilic photosensitizer under unfavorable conditions resulted in contamination with a hydrophobic dye. The absorption spectrum of the hydrophobic dye was characterized by a new band at 514 nm that was absent in the absorption spectrum of the photosensitizer. There was no spectral overlap between this absorption band and the absorbance of the photosensitizer. Therefore, presence of the band at 514 nm allowed us to detect contamination of the photosensitizer substance with the hydrophobic dye. It was established that the optimal photosensitizer concentration for purity testing is ca. 0.8 mmol/L, when as little as 0.6 wt. % of the impurity can be detected. The developed method is not time consuming and requires accessible equipment only. Data obtained with this method was verified with the aid of liquid chromatography-mass spectrometry.